2012
DOI: 10.1007/s00198-012-2189-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term HIV infection and antiretroviral therapy are associated with bone microstructure alterations in premenopausal women

Abstract: Summary We evaluated the influence of long-term HIV infection and its treatment on distal tibia and radius microstructure. Premenopausal eumenorrheic HIV-positive women displayed trabecular and cortical microstructure alterations, which could contribute to increased bone fragility in those patients. Introduction Bone fragility is an emerging issue in HIVinfected patients. Dual-energy X-ray absorptiometry (DXA) quantified areal bone mineral density (BMD) predicts fracture risk, but a significant proportion of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
(40 reference statements)
0
29
1
Order By: Relevance
“…Coinfected men had compromised bone strength at the narrow neck and shaft of the proximal femur, and the smaller cortical area of the shaft coupled with normal bone width (ie, periosteal circumference) was consistent with endocortical bone deficits, similar to our findings with pQCT. Finally, 2 studies used high-resolution pQCT to evaluate bone microstructure in ART-treated HIV-infected premenopausal women [49] and young men [50], and both identified trabecular and cortical bone deficits compared with HIV-uninfected controls.…”
Section: Discussionmentioning
confidence: 99%
“…Coinfected men had compromised bone strength at the narrow neck and shaft of the proximal femur, and the smaller cortical area of the shaft coupled with normal bone width (ie, periosteal circumference) was consistent with endocortical bone deficits, similar to our findings with pQCT. Finally, 2 studies used high-resolution pQCT to evaluate bone microstructure in ART-treated HIV-infected premenopausal women [49] and young men [50], and both identified trabecular and cortical bone deficits compared with HIV-uninfected controls.…”
Section: Discussionmentioning
confidence: 99%
“…Calmi and colleagues found a decrease in the trabecular number and trabecular density in the tibial bone of HIV + women using ART when compared with HIV − women . They also found a decrease in the cortical density of the radius of HIV + women when compared with controls . In postmenopausal African American and Hispanic women, the cortical area and thickness of the tibia were approximately 12% lower in HIV + than in HIV − individuals .…”
Section: Bone Mineral Density and Bone Quality In Hiv‐positive Subjectsmentioning
confidence: 98%
“…Changes in trabecular and cortical bone structure have been described in premenopausal and postmenopausal women, as well as in young and middle‐aged men . Calmi and colleagues found a decrease in the trabecular number and trabecular density in the tibial bone of HIV + women using ART when compared with HIV − women . They also found a decrease in the cortical density of the radius of HIV + women when compared with controls .…”
Section: Bone Mineral Density and Bone Quality In Hiv‐positive Subjectsmentioning
confidence: 99%
“…In 22 HIV-infected premenopausal women, Calmy et al 48 reported significantly lower tibial trabecular bone density and trabecular number, and a significantly lower cortical density in the radius when compared with non-infected controls. In 46 HIV-positive postmenopausal women, tibial cortical thickness and cortical area were significantly lower than control values, but no differences were seen in the radius.…”
Section: Pathophysiology Of Bone Loss Associated With Hiv Infectionmentioning
confidence: 99%